ANALISIS CITRAAN DALAM BUKU KUMPULAN PUISI “LILIN” KARYA WIWID WINARISIH DENGAN PENDEKATAN OBJEKTIF - Laia, Septian Ester Tegar Wati (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The problem in this research lies in visual imagery because it discusses too much visual imagery, resulting in a lack of other imagery variants. This research was motivated by the researcher's curiosity about the imagery in Wiwid Winarsih's poetry collection "Lilin". The aim of this research is to describe the types of imagery contained in the poetry collection "Lilin" by Wiwid Winarsih. The type of research used in this research is a qualitative approach with descriptive methods. The data collection technique used by researchers is documentation techniques. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. In this research, the data validity checking technique used was time triangulation. The results of this research show that the imagery contained in the 12 poems in the poetry collection by Wiwid Winarsih's "Lilin" has a total of 40 quotations. Imagery found in the poetry collection "Lilin" by "Lilin" Wiwid Winarsih. among others; The most dominant imagery found in the poetry collection "Lilin" by Wiwid Winarsih is visual imagery and the second is auditory imagery, tactile imagery, while the least numerous imagery is olfactory imagery and tasting imagery. The suggestions put forward by the researcher are 1) the results of this research can be used as a reference in creating a literary work, one of which is poetry, 2) poetry readers can use this research as information material to review the elements of imagery in poetry, 3) it is recommended for future researchers , can use this research as reference material for conducting subsequent research.